Chapter 3 Behavioural biology, conservation genomics, and population viability (Open Access) - Wright, David J (Taylor & Francis, 2022)
This is the first book on captive animal behaviour, applied to welfare. It enables all aspects of zoo husbandry and management (nutrition, enclosure design, handling & training, enrichment, population management) to be based on a sound knowledge of the species, its evolutionary and natural history.